2009
DOI: 10.1073/pnas.0812822106
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of CalDAG-GEFI and CalDAG-GEFII predicts the severity of motor side-effects induced by anti-parkinsonian therapy

Abstract: Voluntary movement difficulties in Parkinson's disease are initially relieved by L-DOPA therapy, but with disease progression, the repeated L-DOPA treatments can produce debilitating motor abnormalities known as L-DOPA-induced dyskinesias. We show here that 2 striatum-enriched regulators of the Ras/Rap/ERK MAP kinase signal transduction cascade, matrix-enriched CalDAG-GEFI and striosome-enriched CalDAG-GEFII (also known as RasGRP), are strongly and inversely dysregulated in proportion to the severity of abnorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
52
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 41 publications
3
52
0
Order By: Relevance
“…This molecule is expressed exclusively in neurons of the CNS, and, more importantly, it is not linked to cell-survival pathways because it operates as a signaling integrator downstream of glutamate-and dopaminemediated signals (18), which are dysregulated in LID (1-4). In addition, unlike observations for other ERK regulators (27), the absolute amount of the Ras-GRF1 proteins does not change in dyskinetic animals, making this molecule an appealing drug target because the efficacy of a Ras-GRF1-specific treatment would not be diminished by a compensatory elevation of its expression. Our proof-of-concept study in the mouse shows that Ras-GRF1 deficiency can prevent the development of LID, possibly delaying its onset.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This molecule is expressed exclusively in neurons of the CNS, and, more importantly, it is not linked to cell-survival pathways because it operates as a signaling integrator downstream of glutamate-and dopaminemediated signals (18), which are dysregulated in LID (1-4). In addition, unlike observations for other ERK regulators (27), the absolute amount of the Ras-GRF1 proteins does not change in dyskinetic animals, making this molecule an appealing drug target because the efficacy of a Ras-GRF1-specific treatment would not be diminished by a compensatory elevation of its expression. Our proof-of-concept study in the mouse shows that Ras-GRF1 deficiency can prevent the development of LID, possibly delaying its onset.…”
Section: Discussionmentioning
confidence: 99%
“…affected in a rat model of LID (27). To determine whether Ras-GRF1 and its close homolog Ras-GRF2 show similar alterations, we examined the levels of these proteins (p140 Ras-GRF1 and p135 Ras-GRF2 ) in the mouse striata by Western blot analysis (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A number of molecular changes that are thought to underlie clinical manifestation of dyskinesia have been reported, including alterations in striatal dopamine receptors and their downstream signaling targets (summarized in Table 1) (3)(4)(5)(6)(7). The article in a recent issue of PNAS by Ann Graybiel and colleagues (8) reports that CalDAG-GEFI and CalDAG-GEFII, regulators of the ERK signaling pathway, may be key mediators of dyskinesia expression in the striatum.…”
mentioning
confidence: 99%
“…This idea implies that such segregation of information flow through the 2 compartments is maintained and transmitted to the output structures of the basal ganglia. Graybiel and coworkers (8) showed that the opposing changes of the 2 CalDAGGEFs mirror this type of segregation, suggesting that abnormal motor patterns may be functionally segregated. Of note, only the combination of 6-OHDAinduced lesion and the L-DOPA treatment, which produced abnormal movements, were able to cause major modifications in the striatal expression of these 2 CalDAG-GEFs.…”
mentioning
confidence: 99%
See 1 more Smart Citation